Extragastrointestinal Stromal Tumor (EGIST) in 59 Years Old Male: A Rare Case Report - Mahendra Dewi, I Gusti Ayu Sri; Ekawati, Ni Putu; Gotra, I Made; Krisnuhoni, Ening; Paskarani, Putu Erika; Hutapea, Yuliance Nurhawati (Indonesian Journal of Cancer, 2025)
Introduction: GISTs usually occur in older adults with a median age of about 60–65 years. The incidence rate between men and women is equal (1:1). The most common location of GISTs is the stomach which accounts for 60%, followed by the jejunum and ileum around 30%, duodenum 5%, and colorectal 5% and a small percentage of cases occur in the esophagus, appendix, gallbladder, and extraintestinal areas such as the mesentery, omentum, and retroperitoneum. Case Presentation: A 59-year-old male, suffered from a lump under the umbilicus 3 months before admission to the hospital. The results of the ultrasound examination showed a mass in the superior area of the bladder, and the mass did not appear to infiltrate the intestines, bladder, umbilicus, and surrounding organs. The biopsy tissues showed spindles and round-to-oval morphology with eosinophilic cytoplasm. Mitoses 65/50 High Power Field In addition, immunohistochemistry examination showed positive stains in DOG 1, CD117, SMA, CD 34, and negative for S100.Conclusion: Extragastrointestinal stromal tumor is a rare tumor. Based on, clinical, imaging, histopathological, and immunohistochemical examination, this case was diagnosed as an extragastrointestinal stromal tumor, spindle cell type.